Effect of fracture distribution on the triaxial shear behavior of loess - Chen, Lijie; Ma, Penghui; Zhao, Junyan; Xie, Fei; Yan, Ruixin; Leng, Yanqiu; Nan, Jingjing (Frontiers in Earth Science, 2023)
Fractures are widespread phenomena on loess slopes in northwestern China. Fractures are of various types and have different distribution patterns, and they are important factors affecting the mechanical properties of loess. In this paper, the effect of different fracture distribution modes (fracture angle, fracture position and fracture combination) on the shear strength of loess is investigated by carrying out consolidated undrained triaxial shear tests. The results show that the existence of fractures in loess can significantly weaken the strength of the soil under consolidated undrained conditions. Compared with unfractured loess, fractures weaken the shear strength of loess mainly by weakening the cohesion. The internal friction angles of fractured loess, however, are hardly affected by the existence of fractures and the fracture distribution mode. Furthermore, a comparison of three fracture distribution modes, namely, the fracture angle, position and combination, reveals that the fracture angle is the most significant factor weakening the loess strength, followed by fracture combination, and the least is fracture position. In addition, confining pressure increments can greatly improve the shear strength of both unfractured and fractured loess, and confining pressure increments can inhibit the weakening effect of fractures on loess strength.